Study of the Biochemical Biodiversity of Camel Milk - Sara Bouhaddaoui; Rachida Chabir; Faouzi Errachidi; Lahsen El Ghadraoui; Bouchra El Khalfi; Meryem Benjelloun; Abdelaziz Soukri (The Scientific World Journal)
Due to its balanced composition in basic nutrients, its richness in vitamins and in minerals, camel milk has a special place in the daily diet of southern populations. The present study aimed at examining some physicochemical and biochemical characteristics of camel milk (Camelus dromedarius) in Morocco. To achieve this aim, three batches of samples of camel milk were collected from various regions (Dakhla, Errachida, and Fès-Meknes) undergoing physicochemical and biochemical analyses. Results showed that Moroccan camel milk is characterized by slight hydronium potential (pH=6.5), low Dornic acidity (15°D), low density (1.029 kg/l), and high content of ashes (8.06 g/l). Likewise, samples had a high content of macronutrients (Fats: 34.09 g/l; Proteins: 32.4 g/l; Sugar: 49.8 g/l) and micronutrients (Vitamin C: 27.53 mg/l; Flavonoids: 29.05 mg EQ/l: total phenolic compounds: 35.45mg GAE/l). In this respect, working on multiple specimens from different Moroccan regions highlighted an analytical diversity from the south to the north. Comparative study of samples from numerous territories all over the world has confirmed this diversity. North African milk is characterized by high content of proteins, fats, and sugar. On the other hand, oriental milk is peculiarized by high vitamin C content.